Aspek Corporate, User, dan Product Pada Citra Merek terhadap Loyalitas Pelanggan di PT. Saudara Cipta Sukses, Deli Serdang - Melia Windya Yolanda; Elserra Siemin Ciamas; Dewi Anggraini; Wilbert Jovando; Supriyanto (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
Every company is required to compete competitively in increasing the intensity of the number ofcompetitors. One of them is by paying attention to the company's brand image so that it can meet thewants and needs of customers in order to maintain customer loyalty. In this research, it is hoped that itwill be found how the influence of brand image on customer loyalty at PT. Saudara Cipta Sukses.. Theresearch method used is quantitative associative and uses purposive sampling technique where thenumber of respondents is 34 shop owners who have made repeat purchases at least 2 times each monthstarting from January 2022 to April 2022. The big influence of brand image on customer loyalty at PT.Saudara Cipta Sukses can be seen from the determination (R2) the percentage is 70.7%. With thiscoefficient of determination, it can be concluded that customer loyalty is influenced by Brand Image onaspects of the Company (Corporate Image), Consumer Aspects (Usher Image) and Product Aspects(Product Image) by 70.7%, while the remaining 29.3% is contributed by other factors. which can beexplained by other variables outside the model in this study.